BAHASA VERBAL SAKSI KORBAN DALAM MENGUNGKAP KASUS KEKERASAN DALAM RUMAH TANGGA (KDRT) DI WILAYAH HUKUM POLRESTA BANJARMASIN - NFN Hestiyana (Kandai, 2017)
This study discusses the verbal language of witnesses in uncovering cases of domestic violence in the jurisdiction of Banjarmasin Police by using the Halliday consept and forensic linguistics approach. The purpose of this study is to describe the verbal language in revealing the victim witness violence in the home (domestic violence) in the jurisdiction of Banjarmasin Police. The method used in this research is the descriptive qualitative method. The procedure of this study conducted in three stages, namely: 1) collecting data; 2) analyzing the data that has been provided; and 3) presenting the results of the data analysis. The data in this research are speeches of witness in domestic violence cases which were experienced and reported to the police, in January 2017. Data were collected by using the following techniques: 1) observation, 2) documentation, and 3) interview. The analysis shows that there are four functions of language used by the victim witness in uncovering cases of domestic violence, namely: 1) the personal function, 2) regulatory function, 3) representation function, and 4) heuristic function.